164 Early haemodynamic changes and myocardial injury after transfemoral transcatheter aortic valve implantation (TAVI). (9th June 2011) - Dworakowski, R; Bhan, A; Brickham, B; Wendler, O; Monaghan, M; Shah, A M; MacCarthy, P
Abstract : Purpose: Transfemoral (TF) TAVI is a novel procedure for the treatment of severe aortic stenosis, without the need for thoracotomy or cardiopulmonary bypass. The procedure results in almost instantaneous normalisation of transvalvular gradients, but little is yet known about the periprocedural haemodynamic effects. We aimed to describe these effects using 3D and tissue Doppler (tD) transthoracic echocardiography (TTE) and Cardiac Output monitoring. Methods: In 16 patients undergoing TF TAVI haemodynamics were characterised with a number of tD and 3D TTE measurements. These were taken at multiple time points (baseline, 6 and 24 hours post procedure). Calculated volumetric parameters included 3D end-diastolic volume (EDV) and end-systolic volume (ESV), stroke volume (SV) and 3D LA volume (LAV). Diastolic function was monitored using the indices mean E:E′ and systolic function/contractility was measured with dP/dt max and early peak systolic velocity (S′). The FloTrac system (consisting of the Vigileo monitor and sensor), uses a clinically validated algorithm to provide continuous cardiac output (CO), stroke volume (SV) and systemic vascular resistance in real-time. Results: TAVI resulted in an immediate increase in cardiac output (3.7 (baseline), 4.6 (6 h) 4.5 l/min (24 h), p<0.5 baseline vs 6 h and 24 h) with no significant change in systemic vascular resistance (1162, 1292 and 1367 dyn*s/cm 5 ). However, 6 h post-TAVI there was a significant decrease in systolic function as measured by dP/dt max/EDV (see Abstract 164 figure 1A ) and co-existent impairment of diastolic function as indicated by medial E:E′ values (see Abstract 164 figure 1B ), which was associated with an appropriate increase in LA volume (70.3, 82.6 and 72.8 ml, p<0.05 baseline vs 6 h). Following this, there was a recovery of both systolic and diastolic indices. In addition, another marker of systolic function, S′ increased after 24 h (6.4, 6.6, 8.2 cm/s, p<0.05 baseline vs 24 h and 6 h vs 24 h). Concurrent with this recovery, we observed a significant decrease in EDV and ESV at 24 h post-TAVI (EDV: 94.9 to 83.4 ml (p<0.05); ESV 41.9 to 33.5 ml (p<0.05)). These changes in haemodynamics were associated with significant increase of troponin I levels at 24 h and increase in CK-MB at 6 h after the procedure (troponin: 0.06 vs 1.19 μg/l, p<0.05; CK-MB 1.6 vs 6.6 μg/l, p<0.05). Conclusion: Successful TF TAVI results in an immediate improvement in cardiac output. However, overlying this, within the first 24 h both systolic and diastolic dysfunction occurs. The rise in the markers of myocardial injury suggest this may be due to myocardial stunning and/or some periprocedural myocardial damage. Recovery of contractility is observed after 24 hours.